Do Workers Accept Lower Wages in Exchange for Health Benefits? - Olson, Craig A. (Journal of Labor Economics, 2002)
Compensating wage theory predicts that workers receiving more generous fringe benefits are paid a lower wage than comparable workers who prefer fewer fringe benefits. This study tests this prediction for employer‐provided health insurance by modeling the wages of married women employed full‐time in the labor market. Husband's union status, husband's firm size, and husband's health coverage through his job are used as instruments for his wife's own employer health insurance benefits. The estimates suggest wives with own employer health insurance accept a wage about 20% lower than what they would have received working in a job without benefits.